Sustainable Management and Treatment of Explosive Solid Waste: Approaches for Civil and Military Applications - Alves, Ana Beatriz Bastos; Mathias, Alvaro Luiz (Revista Gestão & Sustentabilidade, 2025)
Energetic materials release their chemical energy through slower exothermic reactions, as observed in propellants, or instantaneously, as with explosives. This narrative review provides a comprehensive and holistic perspective on the complex lifecycle of explosive solid waste (E-SW) and related energetic materials. It covers key aspects such as explosive waste research, definition, classification, history, applications, management complexities, environmental and health impacts, disposal methods, and green innovations. While explosives are critical in both civil and military applications, they pose significant environmental and health risks throughout their lifecycle. E-SW management remains an urgent yet underexplored area in scientific literature, especially compared to other explosive-related topics. Traditional disposal methods, like open burning and detonation, result in significant pollution, contaminating soil, water, and air. Despite this, these methods persist due to the lack of safer, economically viable alternatives. Innovative solutions such as biological treatments show promise in mitigating environmental damage, particularly in decontaminating metal residues for recycling. However, challenges in scalability and effectiveness remain. Prioritizing the development of biodegradable energetic materials and designing devices with safer dismantling procedures are essential. The pursuit of green innovations and further research is crucial to refining E-SW management strategies, reducing pollution, and protecting ecosystems and human health.